Isolation of Alkaloid Compounds from Ethanol Extract of Rimpang Galang Merah (Alpinia purpurata (Vielli) K. Schum) and nanoparticle production from its Alkaloid Extract. Comparative Study of Antibacterial Properties on Staphylococcus aureus and Eschericia - Vatara Artanta Silalahi; Enny Fachriyah; Pratama Jujur Wibawa (Jurnal Kimia Sains dan Aplikasi, 2018)
Isolation of alkaloid compounds from ethanol extract of red galangal rhizomes to compare their antibacterial properties with extracts formed into nanoparticles has been performed. The isolation of the alkaloid compounds was performed successively by salting using (i) hydrochloric acid (HCl) to pH 3 (when in ethanol) and using (ii) ammonium hydroxide (NH4OH) to pH 10 (when in chloroform). The alkaloid concentrated extract was obtained after chloroform was evaporated using a rotary evaporator. This alkaloid extract was then carried out by TLC silica gel GF254 using chloroform eluent: ethyl acetate (9: 2) to obtain a specific alkaloid type as a single/pure compound. Test of alkaloid purity successfully isolated by one-dimensional or two-dimensional TLC using various types of eluents with varying degrees of polarity, ie acetone, chloroform, ethyl acetate, ethanol and chloroform: ethyl acetate mixture (9: 2). Isolates of pure alkaloids were analyzed using UV-Vis spectrophotometers), FTIR and (LC-MS). The obtained alkaloid isolates were isokuinolin group with UV-visible absorption characteristics at maximum wavelength (λmaks) of 212 nm, 227 nm and 261 nm. The alkaloid isolate also showed the presence of functional groups -OH, -C-H, C = O, C = C, C = N, C-N, and C-O with molecular weight of 262.90 g/mol. The production of ethanol extract nanoparticles containing alkaloid-containing red galangal (EEAlkNPs) was performed using a top-down approach using ultrason (40 kHz, 2x50 watt) for 10 minutes. The EEAlkNPs size was determined by the dynamic light scattering method (DLS) using the Particles size analyzer (PSA) tool and obtained an average particle size of 220.2 nm. The antibacterial properties of EEAlkNPs were tested by disc diffusion method for the culture of S.aureus and E.coli bacteria. It is known that the antibacterial properties of EEAlkNPs are relatively larger than the original ethanol extract at the same concentration, ie, 2000 parts per million (bpj) or g / L.